RESTful information exchange among engineering tools for wireless sensor networks in home automation - Jia Wang; Zhibo Pang; Bag, Gargi; Johansson, Morgan E. (2015 International Conference on Computer, Information and Telecommunication Systems (CITS), 2015)
In home automation (HA) industry, various roles are involved such as device manufactures, system integrators, and installers. Engineering tools are required not only to improve installation efficiency and reduce the engineering cost, but also to simplify information exchange among different stakeholders. In this paper, a RESTful information exchange method among installer-friendly engineering tools is proposed and demonstrated. It can simplify the engineering workload and optimizes device interoperability among different wireless technologies. Finally, a prototype is implemented to verify the technical feasibility of the proposed RESTful based method.